Single‐phase hybrid multilevel inverter topology with low switching frequency modulation techniques for lower order harmonic elimination. Issue 17 (5th February 2021) - Siddique, Marif Daula; Bhaskar, Mahajan Sagar; Rawa, Muhyaddin; Mekhilef, Saad; Memon, Mudasir Ahmed; Padmanaban, Sanjeevikumar; Almakhles, Dhafer J.; Subramaniam, Umashankar
Abstract : A new single‐phase asymmetrical multilevel inverter (MLI) is presented in this study. The proposed topology generates a staircase output voltage waveform with a maximum number of levels using less number of components compared to several existing and recent topologies. The basic module consists of a combination of two isolated DC sources with ten switches that produce all the possible number of levels. Other advantages of the proposed MLI include improved output voltage performance and a low blocking voltage of the switches. The low switching frequency pulse width modulation (LSF‐PWM) technique has been used for the generation of gate pulses. In the LSF technique, selective harmonic elimination (SHE) and fundamental switching frequency PWM techniques have been discussed for the better output voltage waveform. The optimised switching angles with SHEPWM has been calculated using particle swarm optimisation considering the different combination of the elimination of lower order harmonics. Simulation work was carried out using MATLAB/SIMULINK, and a prototype was implemented to validate the proposed MLI module. Simulation and experimental results have been provided in the study to show the performance of the proposed topology with these modulation techniques.